2021
DOI: 10.1029/2020gl090675
|View full text |Cite
|
Sign up to set email alerts
|

A Satellite‐Based Estimate of Convective Vertical Velocity and Convective Mass Flux: Global Survey and Comparison With Radar Wind Profiler Observations

Abstract: Convection is fundamental to atmospheric energetics and general circulation. While the ultimate energy source for Earth's atmosphere comes from the Sun, most of the solar insolation is directly deposited at the surface. Convection redistributes the energy by transporting it from the surface upward into the atmosphere, balancing atmospheric cooling in the infrared, and driving large-scale circulation (e.g., Hartmann, 2016). In doing so, convection also moves momentum, moisture, and chemically important trace co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
3
5
0
Order By: Relevance
“…This choice results in constant profiles of area fraction up to 9 km, thus strongly influencing the results obtained when analyzing the vertical derivatives of mass-flux and its components. The dominant role of convective area fraction in determining mass-flux was suggested in several other studies (e.g., Jeyaratnam et al, 2021;Kumar et al, 2015;Masunaga & Luo, 2016) including LES experiments (e.g., Böing et al, 2012;de Rooy & Siebesma, 2010) and it is confirmed in our study. These results encourage parameterization methods that aim to estimate area fraction and vertical velocity separately (de Rooy & Siebesma, 2010;Peters et al, 2013Peters et al, , 2017Siebesma et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This choice results in constant profiles of area fraction up to 9 km, thus strongly influencing the results obtained when analyzing the vertical derivatives of mass-flux and its components. The dominant role of convective area fraction in determining mass-flux was suggested in several other studies (e.g., Jeyaratnam et al, 2021;Kumar et al, 2015;Masunaga & Luo, 2016) including LES experiments (e.g., Böing et al, 2012;de Rooy & Siebesma, 2010) and it is confirmed in our study. These results encourage parameterization methods that aim to estimate area fraction and vertical velocity separately (de Rooy & Siebesma, 2010;Peters et al, 2013Peters et al, , 2017Siebesma et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…10.1029/2021JD034910 13 of 17 in determining mass-flux was suggested in several other studies (e.g., Jeyaratnam et al, 2021;Kumar et al, 2015;Masunaga & Luo, 2016) including LES experiments (e.g., Böing et al, 2012;de Rooy & Siebesma, 2010) and it is confirmed in our study. These results encourage parameterization methods that aim to estimate area fraction and vertical velocity separately (de Rooy & Siebesma, 2010;Peters et al, 2013Peters et al, , 2017Siebesma et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The observations in Figures 11f and 11l show that the most intense convective updrafts and downdrafts are within the deeper convective cores. This is not surprising and it is consistent with previous observational findings (e.g., Jeyaratnam et al., 2021). Peak values of updraft and downdraft velocities appear in the highest ETH bin, reaching 23.5 m/s and −15.7 m/s, respectively.…”
Section: Mcs Kinematic Statisticssupporting
confidence: 94%